EFEKTIVITAS MEDIA PEMBELAJARAN VIDEOSCRIBE DALAM MENINGKATKAN HASIL BELAJAR EKONOMI KELAS XII MAN 1 SINTANG - Ericha Ericha; Witarsa Witarsa; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the effectiveness of using videoscribe inimproving economic learning outcomes for class XII students of MAN1 Sintang. The research method used is quantitative with a quasiexperimental form. Sources of data in this study were students of classXII IIS 1 as a control class as many as 36 students and XII IIS 4 as anexperimental class as many as 39 students, the data taken to see theeffectiveness of using videoscribe was the learning outcomes ofstudents after the implementation of videoscribe. The results of thestudy were tested using the T-Test test in the experimental class whichshowed a significant difference, namely the increase in learningoutcomes after being given treatment using the vdeoscribe. This studywas also tested using the N-Gein test to find out how mucheffectiveness the use of videoscribe in improving learning outcomes ineconomic subjects for trading company materials, the test resultsshowed a percentage of 46% the effectiveness of using videoscribe inthe experimental class while 18% effectiveness the use of conventionalmethods in the control class. The conclusion that can be drawn is thatthe use of videoscribe in the economics subject matter of tradingcompanies is 28% more effective in improving learning outcomescompared to conventional methods.